High Performance Composite Polymer Electrolytes Doped With Spherical-Like and Honeycomb Structural Li0.1Ca0.9TiO3 Particles - Xiao, Wei; Wang, Zhiyan; Miao, Chang; Mei, Ping; Zhang, Yan; Yan, Xuemin; Tian, Minglei; Jiang, Yu; Liu, Jingjing (Frontiers in Chemistry, 2018)
The spherical-like and honeycomb structural Li0.1Ca0.9TiO3 particles are prepared by spray drying combined with following calcination confirmed by X-ray diffraction (XRD) and scanning electron microscopy (SEM) with energy dispersive X-ray spectrometer (EDS). The poly (vinylidene fluoride-co-hexafluoropropylene) (P(VDF-HFP))-based composite polymer electrolytes (CPEs) modified with the particles are fabricated by phase inversion and activation processes. The characterization results show that the as-prepared CPE membranes possess the smoothest surface and most abundant micropores with the lowest crystallinity with adding the particles into the polymer matrix, which results in high ionic conductivity (3.947 mS cm−1) and lithium ion transference number (0.4962) at ambient temperature. The interfacial resistance can be quickly stabilized at 508 Ω after 5 days storage and the electrochemical working window is up to 5.2 V. Moreover, the mechanical strength of the membranes gains significant improvement without lowering the ionic conductivity. Furthermore, the assembled coin cell can also deliver high discharge specific capacity and preserve steady cycle performance at different current densities. Those outstanding properties may be ascribed to the distinctive structure of the tailored spherical-like and honeycomb structural Li0.1Ca0.9TiO3 particles, which can guarantee the desirable CPEs as a new promising candidate for the polymer electrolyte.